\(\displaystyle\frac{{\sqrt{{{4}\times{7}+{2}^{{3}}}}}}{{{3}^{{2}}–{5}}}=\)

\(\displaystyle=\frac{{\sqrt{{{4}\times{7}+{2}\times{2}\times{2}}}}}{{{3}\times{3}–{5}}}=\)

\(\displaystyle=\frac{{\sqrt{{{28}+{8}}}}}{{{9}–{5}}}=\)

\(\displaystyle=\frac{\sqrt{{36}}}{{4}}=\)

\(\displaystyle=\frac{{6}}{{4}}=\frac{{3}}{{2}}\)

\(\displaystyle=\frac{{\sqrt{{{4}\times{7}+{2}\times{2}\times{2}}}}}{{{3}\times{3}–{5}}}=\)

\(\displaystyle=\frac{{\sqrt{{{28}+{8}}}}}{{{9}–{5}}}=\)

\(\displaystyle=\frac{\sqrt{{36}}}{{4}}=\)

\(\displaystyle=\frac{{6}}{{4}}=\frac{{3}}{{2}}\)